GC-MS ANALYSIS OF BIOACTIVE COMPONENTS ON AERIAL PARTS OF GAULTHERIA FRAGRATISSIMA WALL - S.Padmavathy; N.NAIR, DHANYA; T.SHANTHI (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Medicinal plant species are being used as folk medicine by various tribal and local communities in Tamilnadu as well as all over India since ancient days. The present study of phytochemical analysis of aerial parts of Gaultheria fragratissima Wall. was extracted with methanol and analysed using GC-MS. Nearly fifteen bioactive chemical compounds were identified in crude extracts. Predominantly, m-Ethylbenzonitrile, 1-Mehtoxy-1-buten-3-yne, 4-Fluorobenzyl alcohol, 5-Methylcyclopent-1-ene-1-carboxyl, Methyl Salicylate, 2-Hexenal, 2ethyl- and Cyclohexane, 1, 3-dimethyl-2-methyl compounds were present. This analysis revealed that the existence of m-Ethylbenzonitrile and 1-Mehtoxy-1-buten-3-yne as major constituents. These different active phytochemicals have been found to possess a wide range of biological applications. Â Â Keywords: Medicinal plant, GC-MS, Gaultheria fragratissima, Phtocompounds Â